Effects of blood flow restriction training on sports performance in athletes: a systematic review with meta-analysis - Li, Rui; Chee, Chen S.; Kamalden, Tengku F.; Ramli, Alif S.; Yang, Kun (Edizioni Minerva Medica, 2024)
INTRODUCTION: Blood flow restriction training (BFRT) is an effective training method to improve sports performance in healthy athletes. Nevertheless, a systematic review with meta-analysis regarding how BFRT affects sports performance in athletes is still lacking. Consequently, the study attempted to expand and consolidate the prior studies regarding the effect of BFRT on technical and physical performance in athletes. EVIDENCE ACQUISITION: This study was based on PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyzes) statement guidelines for a systematic review of the academic databases Scopus, Web of Science, PubMed, EBSCOhost (SportDiscus), and Google Scholar. The PEDro scale was used to assess the methodological quality of the included publications, which ranged from moderate to high quality. The systematic review protocol was registered on inplasy.com (INPLASY202380049). EVIDENCE SYNTHESIS: Out of 249 studies identified, 93 articles were evaluated as eligible, and after the screening, 18 studies were finally included in this systematic review. Meta-analysis results showed a significant enhancement on vertical jump height in the BFRT group compared to the control group (SMD=1.39, 95 CI=0.30-2.49, P=0.01). BFRT was able to significantly increase maximal oxygen uptake (SMD=1.65, 95 CI=0.56-2.74, P<0.01). While no significant improvement in sprint time was observed (SMD= -0.18, 95 CI=-1.18-0.82, P=0.115). CONCLUSIONS: The finding suggests that BFRT is beneficial to athletes as this training method can be effective in enhancing physical and technical performance in athletes. Nevertheless, further analysis needs to be conducted to fully determine the effectiveness of the moderators of the intervention on sports performance.